(untitled) (Faces da História, 2019)
O artigo procura elucidar como o diplomata português Luís da Cunha analisou as negociações entre as potências europeias no Congresso de Utrecht, que definiu as condições para o fim da Guerra de Sucessão Espanhola (1702-1714). Atenta-se para a maneira como o diplomata interpretou a atuação dos representantes ingleses ao longo das negociações, em especial no que se refere às demandas da monarquia portuguesa. Para tanto, investiga-se as Memórias da paz de Utrecht, escritas por Cunha durante a realização do Congresso e endereçada à corte a quem servia. As Memórias oferecem um relato minucioso dos desdobramentos e peculiaridades das negociações. The article seeks to elucidate how the portuguese diplomat Luís da Cunha analyzed the negociations between the european potencys in the Congress of Utrecht, which defined the conditions for the end of the Spanish Succession War (1702-1714). This work focuses on how the diplomat interpreted the work of the english representatives throughout the negotiations, especially with regard to the demands of the portuguese monarchy. For this purpose, we investigate the Memórias da Paz de Utrecht, written by Cunha during the Congress and addressed to the court he served. The "Memórias" give a detailed account of the unfolding and peculiarities of the negotiations.